Short stories for upper secondary school students : a genre-based study - Wong, Vui Fun (2005)
Writing short stories is an art that requires considerable knowledge and understanding of both the structure and language used to express meaning. However, studies have yet to provide a conclusive approach that can show how linguistic elements can be used to realise the writer's communicative intentions. In view of the niche in this discipline, this study attempts to investigate the generic structure of short stories written for upper secondary students by using a genre-based approach, and to provide a descriptive account on the move structure and its linguistic realizations. Thirty short stories from different references were randomly selected and analysed to ascertain the move structure. In addition to this, salient linguistic features were also identified to determine how they were used to realise their intended communicative intentions It has been found that there is a pattern of organisation in the short stories Apart from having a five-move structure, each move is distinctively different in its communicative purposes and linguistic realizations The findings of this study would be particularly useful for classroom practitioners in the context of the teaching English as a second language (TESL) as they may help learners use the schematic structure and the varied linguistic choices in writing short stories